Analisis Penyajian dan Pengungkapan Laporan Keuangan Pada Badan Usaha Milik Desa di Desa Pasir Putih Kecamatan Pamona Selatan Kabupaten Poso - Sondakh, Fivany Gebby Hary; Afandi, Dhullo; Tangkuman, Steven J. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2024)
BUMDes are required to prepare financial statements that are accountable, transparent, and comprehensible, as these statements will be answerable to diverse stakeholders, including the government. SAK ETAP is designed and implemented for the majority of small and medium-sized enterprises in Indonesia. It is suitable for BUMDes because they utilize government and community funds as their business capital, necessitating accountability reports that adhere to relevant accounting standards to satisfy various stakeholders. The study aims to examine how BUMDes Pasir Putih presents and discloses its financial statements according to SAK ETAP. The research methodology employed is descriptive qualitative. Findings indicate that BUMDes Pasir Putih's financial statements, which include only balance sheets and income statements, do not fully adhere to SAK ETAP requirements. There are shortcomings in the proper implementation of SAK ETAP guidelines in the financial statement presentation at BUMDes Pasir Putih